Stability Analysis of Surrounding Rock and Treatment Structures in Superlarge Karst Cave of Naqiu Tunnel - HuaWei Chen; Ce Sha (Advances in Civil Engineering)
This study relied on the treatment and construction process of the corridor hall-type large karst cave of Naqiu Tunnel, and field tests and numerical simulation were carried out to investigate the stability of surrounding rock and treatment structures during the tunnel excavation process. From the results of different excavation footages, both the displacement characteristics between the backfill pile-bearing platform-retaining wall compound treatment structures with surrounding rock and the stress changes of the initial support were analyzed. Combining with the field tests and simulation results, it can be obtained that the compound treatment structure under the bias voltage has unequal leftward displacement and settlement. When the distance to excavation surface gets closer, the bias effect will become greater on the horizontal displacement than on the vertical displacement. Both the displacement and stress changes tend to be stable after the excavation is completed, which proves that the treatment structure of the foundation, bearing platform, retaining wall, and lining structure on the steep slope section is stable and effectively suppresses the effect of the surrounding rock bias voltage. All above conclusions can provide theoretical basis and construction reference for similar projects.